Potential of Essential Oils 2018
DOI: 10.5772/intechopen.78008
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Effect of Essential Oils

Abstract: Essential oils are employed in agriculture, medicine and food industries among others, due to their antimicrobial, antiviral, insecticidal and antifungal properties. In this chapter, we will focus on the control of fungal plant pathogens with essential oils. Fungal diseases in agricultural crops and forestry alter the physiology of plants, disrupting their normal functioning, reducing their yield and sometimes causing their death. Recent studies show antifungal effects of many essential oils against plant path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 94 publications
0
9
0
1
Order By: Relevance
“…Essential oils have also been presented in antifungal properties. The fungal diseases can have different consequences on plants such as alterations in their physiology, disturb their usual functioning, reduce their performance and, even, sometimes the loss of the plant [ 58 ]. Different essential oils from plants (and their dominant constituents) have proved antifungal activity against different plant pathogenic fungi [ 59 ].…”
Section: Essential Oils As Antibacterial and Antifungal Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Essential oils have also been presented in antifungal properties. The fungal diseases can have different consequences on plants such as alterations in their physiology, disturb their usual functioning, reduce their performance and, even, sometimes the loss of the plant [ 58 ]. Different essential oils from plants (and their dominant constituents) have proved antifungal activity against different plant pathogenic fungi [ 59 ].…”
Section: Essential Oils As Antibacterial and Antifungal Compoundsmentioning
confidence: 99%
“…According to Isman and Machial [ 59 ], their action mechanisms is unknown but can be linked to their capacity to dissolve/disrupt the integrity of the fungi’s membranes and cell walls. According to Arraiza et al [ 58 ], in different studies, the antifungal properties are based on the inhibition of fungal mycelial growth in vitro. However, it is necessary to be careful with the use of essential oils because many of these oils (and their pure compounds) can present high phytotoxicity for plants (even in concentrations slightly higher than those necessary for the control of fungi), possibly due to plant cells being affected by the same mechanism [ 59 ].…”
Section: Essential Oils As Antibacterial and Antifungal Compoundsmentioning
confidence: 99%
“…Essential oils are employed in agriculture, medicine and food industries among others, due to their antimicrobial, antiviral, insecticidal and anti-fungal properties. Recent studies show anti-fungal effects of many essential oils against plant pathogenic fungi, which make them candidates for the development of new fungicidal agents (Arraiza et al, 2018). Sharma et al, 2017 also reported that clove oil as potent antifungal agent that could be used as biofungicide for the control of F. oxysporum f. sp.…”
Section: In Vitro Evaluation Of Different Essential Oils Against F Oxysporum F Sp Lycopersicimentioning
confidence: 99%
“…Diseases caused by plant pathogens significantly contribute to annual loss in crop yield worldwide [ 1 ]. The application of chemical pesticides may be an important component and effective control method of these plant diseases, both representing a serious threat to public health and the environment while also causing resistance in pathogens [ 2 , 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In plants, essential oils (EOs) play a protective role against herbivores, phytopathogenic fungi, and weeds. Essential oils also represent a new class of crop protectants due to their volatility and low toxicity to the environment and have been proposed as an alternative to synthetic pesticides [ 3 , 7 , 8 , 9 ]. Additionally, the probabilities of creating new resistant pathogens by using essential oils as biopesticide agents are low, since their constituents can act as synergists [ 10 ].…”
Section: Introductionmentioning
confidence: 99%